Endometrial changes in Infertile Women with Polycystic Ovary Syndrome after taking Letrozole in Comparison to Clomiphene Citrate - Mahmuda, Ummul Khair; Sultana, Nilufar; Rahman, Florida; Afroj, Sultana; Rahman, Fatema; Yesmin, Forida; Akter Sumi, Mariam; Tasnim, Saria (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Background: The endometrium is a receptor organ for most of the hormones involved in fertility and therefore the study of its morphology is thought to explain the mysteries of implantation failure. Many studies showed that Clomiphene Citrate impairs endometrial development due to antiestrogenic effects and long half-life. Conversely Letrozole shows a positive effect on follicle and endometrium. Objective: To assess the endometrium in infertile Polycystic Ovary Syndrome women by Transvaginal Sonography after giving ovulation induction by Clomiphene Citrate versus Letrozole. Materials and Methods: This Comparative cross-sectional study was conducted on sixty diagnosed Polycystic Ovary Syndrome infertile women in the Reproductive Endocrinology & Infertility Unit of Dhaka medical College Hospital, Dhaka, from January 2021 to December 2021. The patients who took Letrozole is called Letrozole group and who took Clomiphene citrate is called Clomiphene citrate group. Serial folliculometry were done to every patient from Day 7. At day 12, the patients were assessed by Transvaginal Sonography for endometrial study. The hyporesponsive and non-responsive patients took higher dose of clomiphene citrate or letrozole in next cycle and serial folliculometry were done as before. Endometrial thickness, pattern and zone of vascularity was compared between the two groups. Preovulatory S. Estradiol was done in case of optimum response. All the relevant data were collected in a predesigned and pretested case record form. Data was processed and analyzed with the help of the computer program SPSS in version 26. Results: Clomiphene Citrate and Letrozole achieved optimum response in 15(50%) and 21(70%) patients, respectively. The Letrozole group had a significantly greater endometrial thickness than the Clomiphene Citrate group (8.85±1.33 vs.7.37±1.07, p=0.001s). Moreover, the Letrozole group showed a greater number of triple line endometrium (76.2% vs 60.0%, p=0.298ns), grade A (42.9% vs 26.7%, p=0.500 ns ) and Zone 3 vascularity (33.3%vs 22.2%, p=0.325 ) than the clomiphene citrate group. Conclusion: Letrozole induces significantly better endometrial development in terms of endometrial thickness than clomiphene citrate. Bangladesh J Obstet Gynaecol, 2022; Vol. 37(1): 5-13